Development of Certified Reference Material of L-Thyroxine by Using Mass Balance and Quantitative Nuclear Magnetic Resonance - Qiang Zhao; Weifei Zhang; Dan Song; Xirui Zhou; Xianjiang Li; Huan Yao; Wenjing Xing; Hongmei Li; Jian Ma; Peng Xiao (Molecules)
L-thyroxine (T4) is an important hormone for diagnosing and evaluating thyroid function disorders. As outlined in ISO17511, having a certified reference material (CRM) is crucial for ensuring that the results of clinical tests are traceable to the SI-unit. This study employed two principal methods to evaluate the purity of T4, mass balance (MB) and quantitative nuclear magnetic resonance (qNMR), both of which are SI-traceable (International System of Units) approaches. The MB method involved a detailed analysis of impurities, including water, structurally related compounds, and volatile and non-volatile substances. A variety of techniques were employed to characterize T4 and its impurities, including liquid-phase tandem high-resolution mass spectrometry, ultraviolet spectrophotometry, infrared spectroscopy, and both 1H-NMR and 13C-NMR. Additionally, impurities were quantified using Karl Fischer coulometric titration, ion chromatography, gas chromatography–mass spectrometry, and inductively coupled plasma–mass spectrometry. In qNMR, ethylparaben was used as the internal standard for direct value assignment. The results showed T4 purities of 94.92% and 94.88% for the MB and qNMR methods, respectively. The water content was determined to be 3.563% (n = 6), representing the highest impurity content. Ten structurally related organic impurities were successfully separated, and five of them were quantified. Ultimately, a purity of 94.90% was assigned to T4 CRM, with an expanded uncertainty of 0.34% (k = 2).